Acute polymyositis in an adult associated with Mycoplasma pneumoniae infection. Issue 771 (January 1990) - Bennett, M.R.; O'Connor, H.J.; Neuberger, J.M.; Elias, E.
Abstract : A previously healthy adult developed a hitherto unreported major complication of Mycoplasma pneumoniae infection, namely acute polymyositis.